2023
DOI: 10.1002/cam4.6316
|View full text |Cite
|
Sign up to set email alerts
|

Identification of angiogenesis‐related genes signature for predicting survival and its regulatory network in glioblastoma

Abstract: Glioblastoma (GBM) is notorious for malignant neovascularization that contributes to undesirable outcome. However, its mechanisms remain unclear. This study aimed to identify prognostic angiogenesis‐related genes and the potential regulatory mechanisms in GBM. RNA‐sequencing data of 173 GBM patients were obtained from the Cancer Genome Atlas (TCGA) database for screening differentially expressed genes (DEGs), differentially transcription factors (DETFs), and reverse phase protein array (RPPA) chips. Differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Additionally, immunohistochemistry assays demonstrated that COL6A1 was significantly upregulated in tumor tissues of high-risk GBM patients. Their single-cell RNA sequencing work also validated those malignant cells expressed high levels of COL6A1 (Wan et al, 2023). Altieri et al (2019) identified a network of gene mutations associated with survival, including COL5A3 and LAMA2 (p < 0.05).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Additionally, immunohistochemistry assays demonstrated that COL6A1 was significantly upregulated in tumor tissues of high-risk GBM patients. Their single-cell RNA sequencing work also validated those malignant cells expressed high levels of COL6A1 (Wan et al, 2023). Altieri et al (2019) identified a network of gene mutations associated with survival, including COL5A3 and LAMA2 (p < 0.05).…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, immunohistochemistry assays demonstrated that COL6A1 was significantly upregulated in the tumor tissues of high-risk GBM patients. Single-cell RNA sequencing also validated that these malignant cells expressed high levels of COL6A1 [60]. Increased expression of COL6A1 and the vascular endothelial molecular marker cluster of differentiation ( CD31) induced glioma angiogenesis [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood-Brain Barrier's pericyte's disruption and hypoxia sustain small vessel proliferation and, in the small vessels district, the dialogue between cancer cells proteins such Nestin and CD133 and endothelial biomarkers such as CD34 proteins facilitates brain metastasis, sustaining tumor cells circulation and subsequent tissue infiltration (Schiffer et al, 2018). More recently, the development of vascularization in GB was also described using genomic analytical tools, to create a risk prediction model for GB, where prognostic differentially expressed angiogenesis-related genes (PDEARGs) become potentially druggable prognostic biomarkers of regulatory networks and provide valuable insight to tackle the role of neovascularization in these tumors (Wan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%